2020
DOI: 10.1182/blood-2020-142658
|View full text |Cite
|
Sign up to set email alerts
|

Biological Impact of Monoallelic and Biallelic BIRC3 Loss in Del(11q) Chronic Lymphocytic Leukemia Progression

Abstract: Chronic lymphocytic leukemia (CLL) patients harboring 11q22.3 deletion, del(11q), are characterized by a rapid disease progression. One of the suggested genes to be involved in the pathogenesis of this deletion is BIRC3, a negative regulator of NF-κB, which is monoallelically deleted in ~80% of del(11q) CLL cases. In addition, truncating mutations in the remaining allele of this gene can lead to BIRC3 biallelic inactivation, which accounts for marked reduced survival in CLL. Nevertheless, the biological mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the contrary, those with a lower proportion of cells with 11q del showed no significant difference from the wild type. This finding could be explained on the basis of the results in a recent study done by Álamo et al [ 10 ] who, demonstrates that biallelic BIRC3 deletion through 11q del and mutation triggers non-canonical NF-κB signaling, driving BCL2 overexpression and conferring clonal advantage, which could account for the negative predictive impact of BIRC3 biallelic inactivation in CLL.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…On the contrary, those with a lower proportion of cells with 11q del showed no significant difference from the wild type. This finding could be explained on the basis of the results in a recent study done by Álamo et al [ 10 ] who, demonstrates that biallelic BIRC3 deletion through 11q del and mutation triggers non-canonical NF-κB signaling, driving BCL2 overexpression and conferring clonal advantage, which could account for the negative predictive impact of BIRC3 biallelic inactivation in CLL.…”
Section: Discussionmentioning
confidence: 88%
“…The most frequent chromosomal changes are entire chromosome additions, like trisomy 12, and incomplete deletion of one chromosome as 6q, 11q, 17p and 13q. Certain cytogenetic abnormalities, including deletions of 11q or 17p, have poor prognosis [7][8][9][10] Many trials have been done to search for new biomarker for improvement risk stratification of CLL patients outcome [11][12][13]. In this context, Recent reports indicated that the degree of positivity of cytogenetic findings by FISH could have different impact on CLL patients outcome [14].…”
Section: Introductionmentioning
confidence: 99%